Geopolitical «Borderliness» as a Factor in Ukraine’s Positioning in International Relations: the Experience of Ukrainian Discourse at the Beginning of the XXI Century - P. I. Pashkovsky (Проблемы постсоветского пространства)
The article considers the problem of the phenomenon of geopolitical «borderliness» as a factor in the positioning of Ukraine in international relations within the Ukrainian scientific discourse of the early XXI century. The definition of the concept of geopolitical «borderliness» has been presented. It is shown that Ukraine is an average regional power, which is characterized by a «borderliness» geopolitical position. On the modern Ukrainian territory, the Euro-Atlantic, Eurasian, Islamic massif and, accordingly, the «super-ethnic frontiers» of the Western European, Slavic and Islamic civilizations intersect. Concepts of the genesis of ideological and sociocultural differences within Ukrainian society in the regional dimension have been characterized. It is substantiated that the foreign policy orientation of Ukraine has always been a derivative of the interaction of the Euro-Atlantic, Eurasian and Black Sea (South-Eastern) paradigms, which necessitates adherence to the «orientation priority» in international political positioning. It follows from this that it is expedient for the Ukrainian state to be guided by a non-bloc strategy. According to Ukrainian researchers, the entry of Ukraine into allied relations with one of the competing poles can lead to a strategic conflict with another center of power and negative consequences for Ukrainian statehood. To prevent this from happening, Ukraine was recommended to pursue a foreign policy on the basis of a neutral status and the principles of «optimal multi-vector approach». This was confirmed by the Ukrainian sociological research. The geopolitical and socio-cultural «borderliness» determines the «split» of Ukrainian society, which is manifested in the foreign policy orientations of residents of different regions. According to Ukrainian sociologists, traditionally the majority of the population of the West of Ukraine and about half of the Center supported the European integration vector. At the same time, about half of the inhabitants of the Center and the majority of the population of the South and East of Ukraine were supporters of the development of relations with Russia and the Eurasian vector of integration. As the only option for foreign policy positioning that would unite the Ukrainian society of different regions, the achievement of national agreement through a compromise was noted, this was possible only if Ukraine pursued a policy of neutrality and «optimal multi-vector approach».